2020
DOI: 10.18632/aging.202218
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of real-time three-dimensional echocardiography as a tool for evaluating left atrial volume and function in patients with type 2 diabetes mellitus

Abstract: Objective: To assess the value of real-time three-dimensional echocardiography (RT-3DE) in evaluating changes in left atrial volume and function in type 2 diabetes mellitus (DM) and type 2 diabetic nephropathy (DN) patients. Method: 104 control subjects, 109 DN patients, and 111 DM patients were recruited and underwent RT-3DE. Data pertaining to the left atrium were analyzed using the 3DQA software in order to determine left atrial maximum volume index (LAVImax), left atrial pre-systolic volume inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Sustained hyperglycaemia causes myocardial extracellular matrix deposition, increases myocardial cell oxygen consumption of myocardial cells, myocardial hypertrophy and myocardial interstitial fibrosis, leading to the myocardial overall deterioration [24]. Previous studies have been reported the LA morphological and functional abnormalities in T2DM patients [25,26]. This study proved that T2DM patients with normal morphology also had significantly decreased total LAEF, εs, εe, and SRe, which suggests that the most obvious LA dysfunction induced by T2DM mainly occurs in the reservoir and conduit phase.…”
Section: Discussionmentioning
confidence: 99%
“…Sustained hyperglycaemia causes myocardial extracellular matrix deposition, increases myocardial cell oxygen consumption of myocardial cells, myocardial hypertrophy and myocardial interstitial fibrosis, leading to the myocardial overall deterioration [24]. Previous studies have been reported the LA morphological and functional abnormalities in T2DM patients [25,26]. This study proved that T2DM patients with normal morphology also had significantly decreased total LAEF, εs, εe, and SRe, which suggests that the most obvious LA dysfunction induced by T2DM mainly occurs in the reservoir and conduit phase.…”
Section: Discussionmentioning
confidence: 99%